Influência de fluídos biológicos na sobrevivência de Staphylococcus aureus sobre diferentes superfícies secas - Rossi, D. [UNESP]; Devienne, K. F.; Raddi, Maria Stella Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
It is known that the transmission of hospital infections, whether environmental or cross infection, is facilitated by the enhanced survival of microorganisms on dry surfaces that is caused by the presence of biological fluids. To demonstrate the need for care with bodily substances in the routine of cleaning, this study evaluated the influence of some body fluids (blood, urine and artificial saliva), deposited in the same way on various surfaces and allowed to dry, on the survival of Staphylococcus aureus (ATCC 25923). Blood was able to preserve bacterial viability for up to 72 days when deposited on ceramic flooring. Fabric of cotton fiber allowed longer survival than synthetic fabric. These results show that the composition of biological fluid and type of support influence bacterial survival in normal conditions.

Sabe-se que a transmissão de infecções hospitalares, via cruzada ou ambiental, é facilitada pela sobrevivência de microrganismos em superfícies secas que pode ser favorecida pela presença de fluídos biológicos. Visando demonstrar o cuidado com substâncias corporais na rotina de limpeza, esse estudo avaliou a influência de alguns fluídos biológicos (sangue, urina e saliva artificial) na sobrevivência de Staphylococcus aureus (ATCC 25923), depositados de modo similar, sobre diferentes superfícies após secagem. O sangue foi capaz de preservar a viabilidade bacteriana por até 72 dias quando depositado sobre piso cerâmico. O tecido em fibra de algodão permitiu maior tempo de sobrevivência em comparação ao tecido sintético. Esses resultados demonstram que a composição do fluído biológico e o tipo de suporte altera o tempo da sobrevivência bacteriana em condições ambientais. Palavras–chave: Staphylococcus aureus; fluidos biológicos; sobrevivência bacteriana
Influence of biologicalfluids on survival of Staphylococcus aureus on various dried surfaces
Keywords: Staphylococcus aureus; Staphylococcus aureus; fluidos biológicos; sobrevivência bacteriana; Farmacotécnica; Bacterial survival; Biological fluids; bacterial survival; bacterial viability; blood; body fluid; building; ceramics; cotton; disease transmission; hospital infection; saliva; urine